A Comparative Move Analysis of Low and High-Impact Social Science Scopus Journal Articles Written by Reputable Indonesian Authors - Anggia Lyana Julieta; Eri Kurniawan; Arif Husen Lubis (Universitas Pendidikan Mandalika, 2023)
Producing research articles requires clearly, logically, rationally, and empirically substantiating complicated ideas. Regarding that, many professors struggle to have their articles published in highly regarded publications and require references; for instance, the rhetorical move pattern. Many studies have analyzed the rhetorical structure of articles, but few have investigated the rhetorical move of the research articles produced by lecturers by specifically comparing their publications in high-impact versus low-impact Scopus-indexed journals. Using a descriptive-comparative qualitative design, this study seeks to investigate the moves of low-impact and high-impact articles of the two social humanities lecturers of a state university in Indonesia. Eight articles were analyzed through the move framework proposed by Maswana (2015). The results revealed that the rhetorical moves from each section were organized with significant conformities and minor non-conformities.Especially, the authorsemphasized the goals, procedures, and outcomes of the publications in the abstract section. Furthermore, the writers provided references to the existing literature and the goal of the research to assist the reader in understanding the theory applied in the papers. On the other hand, deviations from the norm are displayed in the methodology section due to variations in how the study was conducted, particularly the data processing phase. The authors’ attention to conveying the research’s specific findings and their significance was in the findings and discussion section. The results of this study can be used as a reference for Indonesian researchers who are striving to publish papers in international journals toward a more visible and impactful publication.